IMPLEMENTASI KEBIJAKAN DIGITALISASI RETRIBUSI QRIS (DRQ) DALAM UPAYA OPTIMALISASI PELAYANAN PUBLIK DAN PENINGKATAN PAD RETRIBUSI UPTD RUMAH POTONG HEWAN KABUPATEN INDRAMAYU - Girishanta, Arundhina (Jurnal Investasi, 2024)
Public service delivery is a key indicator in evaluating the performance of local governments, particularly in terms of effectiveness, efficiency, transparency, and accountability. Along with the rapid advancement of information technology, governments are required to innovate in delivering public services, including in managing local levies as a source of Regional Original Revenue (PAD). The Slaughterhouse Technical Implementation Unit (UPTD RPH) under the Department of Food Security and Agriculture in Indramayu Regency has experienced several issues in its levy collection and deposit system, which was previously conducted manually, resulting in inefficiencies, delays, and potential revenue leakage. To address these challenges, a policy innovation in the form of QRIS-based levy digitalization (DRQ) was introduced. This system utilizes the Quick Response Code Indonesian Standard (QRIS) as a non-cash payment mechanism. The implementation of this policy is expected to enhance public service quality while optimizing local revenue through a faster, more transparent, and accountable transaction system. This study aims to analyze the implementation of the DRQ policy in improving public service delivery and increasing PAD, as well as to identify the supporting and inhibiting factors influencing its implementation. This study employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving key informants, including representatives from the Department of Food Security and Agriculture, the Regional Financial Agency, banking institutions, and service users such as cattle and poultry slaughtering entrepreneurs. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the policy implementation. The findings indicate that the implementation of QRIS-based levy digitalization has a significant positive impact on improving public service quality and optimizing local revenue. The adoption of a non-cash payment system enhances efficiency in terms of time and cost, accelerates transaction processes, and increases transparency and accountability in levy management. Furthermore, the implementation of DRQ helps minimize illegal levies and improves the performance of public service officers in delivering more professional, responsive, and technology-based services. However, several challenges remain, including low digital literacy among service users, limited access to technological devices and banking services, and resistance to transitioning from manual to digital systems. Therefore, continuous efforts such as socialization, technical assistance, and strengthening coordination among stakeholders are necessary to ensure the sustainability and effectiveness of the policy. With adequate support, QRIS-based levy digitalization has strong potential to become a model for public service innovation that can be replicated in other sectors to achieve good governance.